Diabetes in older people: new insights and remaining challenges. Issue 4 (April 2015) - Sinclair, Alan; Dunning, Trisha; Rodriguez-Mañas, Leocadio
Summary Diabetes in ageing communities imposes a substantial personal and public health burden by virtue of its high prevalence, its capacity to cause disabling vascular complications, the emergence of new non-vascular complications, and the effects of frailty. In this Review, we examine the current state of knowledge about diabetes in older people (aged ≥75 years) and discuss how recognition of the effect of frailty and disability is beginning to lead to new management approaches. A multidimensional and multidisciplinary assessment process is essential to obtain information on medical, psychosocial, and functional capabilities, and also on how impairments of these functions could limit activities. Major aims of diabetes care include maintenance of independence, functional status, and quality of life by reduction of symptom and medicine burden, and active identification of risks. Linking of therapeutic targets to individual functional status is mandatory and very tight glucose control is often not necessary. Hypoglycaemia remains an important avoidable iatrogenic event. Quality diabetes care in older people remains an important challenge for health professionals.